2002
DOI: 10.1002/humu.10069
|View full text |Cite
|
Sign up to set email alerts
|

GeneTests-GeneClinics: Genetic testing information for a growing audience

Abstract: The development and usage of two companion NIH-funded genetic testing information databases, GeneTests (www.genetests.org) and GeneClinics (www.geneclinics.org), now merged into one web site, reflect the steadily increasing use of genetic testing and the expanding audience for genetic testing information. Established in 1993 as Helix, a genetics laboratory directory of approximately 110 listings, GeneTests has grown into a database of over 900 tests for inherited diseases, a directory of over 500 international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…39 Research laboratories provide genetic testing, including functional analysis, but may face restrictions on communicating results. 40 …”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…39 Research laboratories provide genetic testing, including functional analysis, but may face restrictions on communicating results. 40 …”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…GeneTests, 12 and its related database, GeneReviews, is a site intended primarily for practicing medical geneticists, but it also contains a range of educational materials to help health care providers understand the appropriate use of genetic counseling and testing. [22][23][24] GeneTests contains information on laboratory tests for inherited diseases, including directories of U.S. and international genetics clinics, and GeneReviews contains summaries relating genetic testing information to diagnosis, management, and genetic counseling of specific inherited diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, for these results to be used clinically they must be performed in CLIA-certified laboratories. The website GeneTests (www.genetests.org) serves as a genetic testing resource for the identification of genetic clinics and genetic testing laboratories offering both clinical and research genetic tests (73 ). As of May 2003, the GeneTests website data indicated that genetic tests are available for 962 diseases in either a clinical or research form and that, Table 1.…”
Section: Discussionmentioning
confidence: 99%